Efficacy of different control methods of the rice striped stem borer Chilo suppressalis (Lepidoptera: Grambidae) under water stress conditions in paddy fields - Farzad Majidi-Shilsar; Mohamadreza Yazdani; Aliakbar Ebadi; Mehrdad Amooghli-Tabari (نامه انجمن حشره‌شناسی ایران, 2024)
The control of rice striped stem borer in paddy fields requires the use of all components of integrated pest management. The implementation of these methods is effective if the rice field is in natural conditions in terms of water resources, but in case of drought stress, which one of the methods will be more effective for pest control? In order to answer this question, the present research was carried out in the Rice Research Institute of Iran (Rasht) in 2019 and 2020. In this research, different irrigation methods as the main factor include permanent flooding (every day) and irrigation with intervals of 5, 10 and 15 days and the secondary factor is different control methods including granule application with G10% diazinon insecticide, spraying with fipronil SC5% insecticide, biological control (release of Trichogramma wasp + use of commercial formulation of Bacillus thuringiensis subsp. kurstaki), a combination of methods (chemical control and biological control) and control (only water spraying) were used. The results of this research showed that the least damage by the rice striped stem pest in the vegetative and reproductive stages of rice plants was in the daily and five-day irrigation treatments with the combined use of methods as well as the granule spraying method in the experimental field. Also, the results of the investigations during the two years of the experiment showed that the highest yield was related to irrigation every day and five days, related to two methods, a combination of methods and a granulation method. In 10- and 15-days’ irrigation, the highest yield was observed in foliar spraying and biological control treatments. Therefore, according to the obtained results, it is recommended to use biological control and foliar spraying with one of the confirmed liquid insecticides to control the rice striped stem borer pest in water stress conditions